Modernism came flying: a micro-history of artistic internationalism and cultural encounters in US-Chilean relations, 1968. Issue 2 (3rd April 2019) - Velázquez, Roberto
ABSTRACT: This work examines the diplomatic, political, and cultural impact of artistic internationalism on US-Chilean relations in 1968. Based on a micro-historical approach to the global Cold War, the article analyses the relationship between modernisation programmes and artistic modernism under the framework of the Alliance for Progress. The case study of 'De Cézanne a Miró', the most expensive art collection sent to Chile by the Museum of Modern Art in New York (MoMA), reveals the creation, exportation, and reception of a distinctive cultural ethos promoted by US agents. The article traces the transnational networks that defined cultural encounters in a crucial year for domestic and global politics.